A new earwig species of the genus Liparura Burr, 1907 (Dermaptera: Forficulidae) from China - Ye, Xiaohan; Kamimura, Yoshitaka; Li, Wenliang; Liu, Xingyue (Zootaxa, 2023)
A new earwig species of the genus Liparura Burr, 1907 of the family Forficulidae, namely L. chongqingensis sp. nov., is described from Chongqing, southwestern China. The new species is characterized by the male forceps basally approached to each other, and each with a small tooth protruding dorsad. A key to the species of Liparura is provided.